Meningkatkan Semangat Siswa dalam Menghafal Al-Qur’an: Pendekatan Guru PAI yang Inspiratif - Fitriansyah, Mahliga; Karimah, Ummah; Febriansyah, Malika; Fadhil, Labil; Mulya Ananda, Riski; Habibi, Ilyas; Shofiyah, Siti (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2025)
Memorizing the Qur'an is a source of pride for a Muslim. It is not uncommon for parents to hope that their child becomes a memorizer of the Qur'an. However, in reality, a child often has little interest in memorizing the Qur'an. This is caused by various factors. The purpose of this research is to determine how enjoyable learning can enhance students' interest in memorizing the Qur'an, which is an extracurricular activity at SMP Nusantara Plus. This research method uses a qualitative research method with a descriptive type. The data collection techniques are through observation and interviews as well as documentation. The data analysis technique used is data reduction based on the Miles Huberman theory. The results of this study indicate that the strategy of PAI teachers in increasing interest in memorizing the Qur'an is by implementing peer tutoring cooperative learning, conducting outdoor learning, applying motivation and reward methods, and collaborating with parents to implement a review schedule at home.